1992
DOI: 10.1042/bj2810627
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+/calmodulin-dependent formation of hydrogen peroxide by brain nitric oxide synthase

Abstract: L-Arginine-derived nitric oxide (NO) acts as an inter- and intra-cellular signal molecule in many mammalian tissues including brain, where it is formed by a flavin-containing Ca2+/calmodulin-requiring NO synthase with NADPH, tetrahydrobiopterin (H4biopterin) and molecular oxygen as cofactors. We found that purified brain NO synthase acted as a Ca2+/calmodulin-dependent NADPH:oxygen oxidoreductase, catalysing the formation of hydrogen peroxide at suboptimal concentrations of L-arginine or H4biopterin, which inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
293
1
4

Year Published

1992
1992
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 521 publications
(325 citation statements)
references
References 29 publications
27
293
1
4
Order By: Relevance
“…This suggests that the in crease in NO hypothesized above to occur with CO2 should be expected to act on the pHcsensitive com ponent of the CO2 responsiveness. This hypothesis fits with the interesting in vitro study of Heinzel et al (1992) showing that NO snythase activity from the brain tissue (cerebellum) is quite markedly in fluenced by pH in that acid pH increases NO pro duction. With acetazolamide, pHi is essentially un changed, while with CO2, pHi becomes acid and NO synthesis might therefore be increased.…”
Section: Discussionsupporting
confidence: 85%
“…This suggests that the in crease in NO hypothesized above to occur with CO2 should be expected to act on the pHcsensitive com ponent of the CO2 responsiveness. This hypothesis fits with the interesting in vitro study of Heinzel et al (1992) showing that NO snythase activity from the brain tissue (cerebellum) is quite markedly in fluenced by pH in that acid pH increases NO pro duction. With acetazolamide, pHi is essentially un changed, while with CO2, pHi becomes acid and NO synthesis might therefore be increased.…”
Section: Discussionsupporting
confidence: 85%
“…The low arginine concentration might also have other consequences, because this amino acid is a precursor for the synthesis of creatine and nitric oxide. In the presence of suboptimal concentrations of arginine, nitric oxide synthase forms superoxide (Heinzel et al, 1992), that reacts avidly with nitric oxide to form peroxinitrite (Heales et al, 1996). Excess free radical production by this and other mechanisms might be a further factor causing cellular damage in anorexia (Roediger, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that in the absence of either -arginine or H % Bip, NOS becomes enzymically uncoupled and reduces molecular oxygen at the expense of NADPH to form reactive oxygen species such as O # − d [48][49][50] and H # O # [22,41]. Moreover, we have recently shown that NOSderived uncoupled catalysis products can accumulate during -arginine turnover and influence enzyme activity [41].…”
Section: Nos Monomerization and O 2 − D : Effect Of Sodmentioning
confidence: 99%
“…During catalysis, NOS can produce significant quantities of reactive oxygen species (O # − d and H # O # ) [21,22,41,50,51] ; H % Bip markedly attenuates this [21,22,37] by a largely unknown mechanism that might involve the haem domain [51]. Importantly, given that NOS-derived reactive oxygen species contribute to enzyme inactivation [41], we considered the possibility that H % Bip stabilizes and protects NOS by interfering with autodamaging O # − d. In agreement with this hypothesis, during enzyme catalysis and in the absence of H % Bip, i.e.…”
Section: Reagent and Nos-bound H 4 Bip : Reaction With O 2 − Dmentioning
confidence: 99%
See 1 more Smart Citation